The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1083/jcb.137.2.509
|View full text |Cite
|
Sign up to set email alerts
|

Isolated P-selectin Glycoprotein Ligand-1 Dynamic Adhesion to P- and E-selectin

Abstract: Leukocyte adhesion to vascular endothelium under flow involves an adhesion cascade consisting of multiple receptor pairs that may function in an overlapping fashion. P-selectin glycoprotein ligand-1 (PSGL-1) and L-selectin have been implicated in neutrophil adhesion to P- and E-selectin under flow conditions. To study, in isolation, the interaction of PSGL-1 with P-and E-selectin under flow, we developed an in vitro model in which various recombinant regions of extracellular PSGL-1 were coupled to 10-μm-diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
131
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(138 citation statements)
references
References 58 publications
7
131
0
Order By: Relevance
“…Moreover, rupture-force histograms, representing the most probable rupture force at a given reproach velocity, always developed a single peak as opposed to regularly spaced force distributions, which would be indicative of the unbinding of oligomeric adhesions (Benoit et al, 2000). The observance of a single significant force histogram for E-selectin/PMN binding is particularly noteworthy, considering the evidence supporting E-selectin binding to glycosphingolipids on the leukocyte cell surface (Alon et al, 1995b;Burdick et al, 2001) as well as multiple regions on PSGL-1 (Goetz et al, 1997). Several distinct E-selectin ligands or simultaneous multiple binding regions might be revealed as a broadened histogram distribution or histograms with multiple peaks (Benoit et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, rupture-force histograms, representing the most probable rupture force at a given reproach velocity, always developed a single peak as opposed to regularly spaced force distributions, which would be indicative of the unbinding of oligomeric adhesions (Benoit et al, 2000). The observance of a single significant force histogram for E-selectin/PMN binding is particularly noteworthy, considering the evidence supporting E-selectin binding to glycosphingolipids on the leukocyte cell surface (Alon et al, 1995b;Burdick et al, 2001) as well as multiple regions on PSGL-1 (Goetz et al, 1997). Several distinct E-selectin ligands or simultaneous multiple binding regions might be revealed as a broadened histogram distribution or histograms with multiple peaks (Benoit et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…PSGL-1 serves as the primary counter-receptor for P-and L-selectin, in that it selectively binds with relatively high affinity and removal or absence of PSGL-1 essentially abrogates P-or L-selectin-mediated rolling (Varki, 1997). E-selectin also binds effectively to PSGL-1 (Goetz et al, 1997;Li et al, 1996), but accumulating evidence supports the concept that glycosphingolipids might also be physiologically relevant Eselectin ligands (Alon et al, 1995a;Bochner et al, 1994;Burdick et al, 2001;Kobzdej et al, 2002). Dynamic rolling assays conducted in the presence of a blocking anti-PSGL-1 mAb (KPL-1) indicated that PSGL-1-coated microspheres are still capable of tethering on E-but not P-selectin substrates (Goetz et al, 1997), supporting the notion that PSGL-1 has binding sites for E-selectin other than the crucial 19 amino acid sequence recognized by KPL-1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have described the N-glycans on PSGL-1 as dispensable for binding [28] and a considerable body of evidence suggest that the selectins bind to Olinked oligosaccharide structures on PSGL-1 [7][8][9][10], [14]. A specific threonine residue has been identified in the NH2-terminal portion of PSGL-1 that is believed to carry the (O-linked) ligand oligosac-charide recognized by P-selectin [29][30][31]. Moreover, results from recent investigations clearly demonstrate that a significant portion of the O-linked structures on PSGL-1 are fucosylated [18], [19], thereby lending further support the involvement of O-linked oligosaccharides in selectin binding.…”
Section: Discussionmentioning
confidence: 99%
“…One strategy for studying the contributions of individual components of that surface is to coat artificial microspheres with purified or recombinant versions of molecules of interest. We and others have used this strategy in the past to investigate the capacity of PSGL-1 and other adhesion molecules to mediate rolling in vitro [27][28][29][30] and in vivo. 20,22,31 Ideally, the properties (size, ligand density, deformabilty, and so forth) of microspheres used for such investigations will closely match those of leukocytes, allowing direct comparisons to be made.…”
Section: Discussionmentioning
confidence: 99%